2015
DOI: 10.18632/genesandcancer.76
|View full text |Cite
|
Sign up to set email alerts
|

Novel high-grade serous epithelial ovarian cancer cell lines that reflect the molecular diversity of both the sporadic and hereditary disease

Abstract: Few cell line models of epithelial ovarian cancer (EOC) have been developed for the high-grade serous (HGS) subtype, which is the most common and lethal form of gynaecological cancer. Here we describe the establishment of six new EOC cell lines spontaneously derived from HGS tumors (TOV2978G, TOV3041G and TOV3291G) or ascites (OV866(2), OV4453 and OV4485). Exome sequencing revealed somatic TP53 mutations in five of the cell lines. One cell line has a novel BRCA1 splice-site mutation, and another, a recurrent B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 80 publications
1
48
0
Order By: Relevance
“…Intriguingly, HGSOC shares similar genomic features with triple negative breast cancer (TNBC) as per reports from Cancer Genome Atlas (TCGA) Network analysis; in particular, the deregulated pathways characterizing HGSOC are very similar to those in TNBC [ 9 ]. Several independent studies have indicated that HGSOC is associated with very high genomic instability and chromosomal aberrations including intrachromosomal breaks and aneuploidy, which incidentally, also typify and drive intratumoral heterogeneity in TNBC [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, HGSOC shares similar genomic features with triple negative breast cancer (TNBC) as per reports from Cancer Genome Atlas (TCGA) Network analysis; in particular, the deregulated pathways characterizing HGSOC are very similar to those in TNBC [ 9 ]. Several independent studies have indicated that HGSOC is associated with very high genomic instability and chromosomal aberrations including intrachromosomal breaks and aneuploidy, which incidentally, also typify and drive intratumoral heterogeneity in TNBC [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These spontaneously immortalized cell lines have been extensively characterized [2225]. Among the 18 cell lines, 17 harbor TP53 mutations, which is the most common somatically mutated gene found in HGS EOCs, while the remaining line fails to express TP53 .…”
Section: Resultsmentioning
confidence: 99%
“…The IC 50 's for carboplatin, as determined by clonogenic survival assay, have previously been reported for TOV3041G, TOV112D, and OV866(2) [27,28]. Carboplatin sensitivity for the OV90 cell line was determined in this study using the same clonogenic assay [27]. Briefly, cells were seeded in a 6-well plate at a density of 750 cells/well that allowed the formation of individual colonies.…”
Section: Clonogenic Survival Assaysmentioning
confidence: 86%
“…Three cell lines [TOV112D, OV90, OV866(2)] are classified as resistant to carboplatin therapy in 2D culture as measured by clonogenic assay, and one (TOV3041G) is classified as sensitive ( Table 1). These cell lines were derived in our laboratory from patient tumor (TOV) or ascites (OV) [27,47] samples. All cell lines were authenticated at the beginning of this study using STR profiling by the McGill University Genome Center (Montreal, Canada).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation